Community readiness for ecotourism management in a royal project development site, Northern Thailand - Promburom T. (2014)
The objectives of the research were to investigate the need and readiness of community in managing community-based ecotourism; and to gather and assemble local knowledge to develop guideline for community-based ecotourism management. The Hmong and Karen stakeholders from 14 villages of Mae Wang and Mae Chaem district, Chiang Mai Province, within responsible area of the Mae Hae Royal Project Development Station, were involved in this study. The participatory community-based ecotourism concept, qualitative research method and participatory action research were conducted. The data were collected by observation, in-depth interview, focus group technique and a formal questionnaire. The tourism program was developed and trialed with volunteer tourists to evaluate their satisfaction. The results were presented to and analyzed together with the stakeholders to develop community-based ecotourism management guideline. It was found that community was willing to have ecotourism and would like to promote their culture and tradition, and way of life including highland agricultural practice to tourists. They thought that the ecotourism could generate supplemental income and culture expression. However, the possible impact on environment, culture and social were concerned, and should be carefully considered and well planned. Most of the stakeholders expressed that the communities were ready for ecotourism, and there should be representatives from the communities participating in the ecotourism management process. Some disagreed concerning with communication problem, hospitality, facilities and road condition. Local knowledge was gathered and integrated into an ecotourism program which was implemented with volunteer tourists. The evaluation of pilot ecotourism program revealed that the tourists were satisfied with and interested in the tour program. They would like to discover folklore. In addition, the folklorists who guided and accompanied the tour could create value added to the program and good impression for tourists. It was suggested that, to develop such ecotourism, the tourism committees be established altogether with agreeable tasks and responsibilities.